PERENCANAAN BENDUNG CIKAWUNG PADA DAERAH NON-CEKUNGAN AIR TANAH DI KABUPATEN CILACAP, JAWA TENGAH - Etika Herdiarti; Shalli Malia Nisa; Robert J. Kodoatie; Hari Nugroho (Jurnal Karya Teknik Sipil, 2013)
Cikawung weir located at Cipari District in Cilacap Regency. Cikawung weir built on the Cikawung river with the catchment area is 121,12 km2. To satisfy irrigation needs in the area around the river of 1020.24 ha, it is necessary to discharge a sufficient pledge. Mainstay discharge calculated by modifying the method FJ Mock. Location Cikawung weir is at a non-groundwater basin covering an area of 98,90 km2 (81,65%) and others are in the area groundwater basin area of 22,22 km2 (18,35%). Both of these regions have different characteristics in generating mainstay discharge. In the ground, at the non-groundwater basin, water flows only in the layer of soil water zone, while in the area groundwater basin water is able to flow to groundwater zone layer. Availability of river water contained on the non - groundwater basin less than groundwater basin area. Cikawung weir flood discharge plan designed by 50-year return period of 425,29 m3 and 1,92 m3 for discharge decision. Cikawung weir is design with specification rounded type of crest with height of  5,5 m, USBR type III of stilling basin, equipped with sand trap, flushing way of sand trap, flushing gate, intake gate, and retaining wall. Cikawung weir construction cost about Rp. 6.911.600.000,00 and a plan of 28 weeks.